Technology Improves Learning in Large Principles of Economics Classes: Using Our WITS - Ball, Sheryl B; Eckel, Catherine; Rojas, Christian (American Economic Review, 2006)
Technology Improves Learning in Large Principles of Economics Classes: Using Our WITS by Sheryl B. Ball, Catherine Eckel and Christian Rojas. Published in volume 96, issue 2, pages 442-446 of American Economic Review, May 2006